Clinical and Endoscopic Profile of Patients with Upper Gastro-Intestinal Bleeding (UGIB) (Journal of Enam Medical College, 2019)
Background: Upper gastro-intestinal bleeding (UGIB) is a cause of significant morbidity and mortality. Prevalence as well as mortality is higher in elderly persons above sixty years because of increasing use of nonsteroidal anti-inflammatory drugs and associated comorbidity. Conventionally upper GI bleeding is divided as variceal and nonvariceal sources and the treatment protocol varies accordingly. There are limited data regarding UGIB in our country.Objective: This observational study was designed to delineate the clinical and endoscopic profile of patients with UGIB in our country.Materials and Methods: This prospective observational study was done in the Department of Gastroenterology in Enam Medical College & Hospital during the period of 2014–2017. Patients with UGIB were followed until discharge or death. Patients were subjected to upper GI endoscopy, preferably within the first 24 hours. Clinical and endoscopic data of 131 patients were compiled and analyzed in this study. The data were analysed using SPSS version 21.0.Results: Among the 131 final participants 101 were male and 30 were female. Mean age of the patients was 43.65 ± 18.63 years. Patients mostly presented with both haematemesis and melaena (66, 50.4% patients), 33.6% with haematemesis only, and 16% patients with melaena only. The most common endoscopic finding was duodenal and or gastric ulcer (57); next common lesions were gastric/duodenal erosions (23), oesophageal varices (13), oesophageal erosions/ulcers (10), corrosive burn (10) and carcinoma (7). Forty patients had history of NSAID intake and gastric/duodenal ulcer and/erosions were the most frequent lesions among them (27). One patient with oesophageal varices died due to rebleeding.Conclusion: In our study peptic ulcer-related bleeding is the most common cause of UGIB. A significant proportion of UGIB is due to corrosive burn (harpic) emphasizing the need for public awareness. Mortality was due to rebleeding.J Enam Med Col 2019; 9(2): 78-83